A pragmatic approach to selective genetic testing in kidney transplant candidates - Nissaisorakarn, Pitchaphon; Fadakar, Paul K.; Safa, Kassem; Lundquist, Andrew L.; Riella, Cristian V.; Riella, Leonardo V. (Frontiers in Transplantation, 2024)
Introduction Advances in the field of genetic testing have spurred its use in transplantation. Potential benefits of genetic testing in transplant nephrology include diagnosis, treatment, risk stratification of recurrent disease, and risk stratification in potential donors. However, it is unclear how to best apply genetic testing in this population to maximize its yield. We describe our transplant center’s approach to selective genetic testing as part of kidney transplant candidate and donor evaluation. Methods Transplant recipient candidates were tested if they had a history of ESRD at age <50, primary FSGS, complement-mediated or unknown etiology of kidney disease, or had a family history of kidney disease. Donors were tested if age <35, were related to their potential recipients with known genetic susceptibility or had a first-degree relative with a history of kidney disease of unknown etiology. A targeted NGS gene panel of 385 genes was used. Clinical implications and downstream effects were monitored. Results Over 30% of recipients tested within the established criteria were positive for a pathogenic variant. The most common pathogenic variants were APOL1 high-risk genotypes as well as collagen 4-alpha-3, -4 and -5. Donor testing done according to our inclusion criteria resulted in about 12% yield. Positive test results in recipients helped with stratification of the risk of recurrent disease. Positive test results in potential donors guided informed decisions on when not to move forward with a donation. Discussion Integrating targeted panel genetic testing into a kidney transplant clinic in conjunction with a selective criteria for testing donors and recipients ensured a reasonable diagnostic yield. The results had implications on clinical management, risk stratification and in some cases were instrumental in directing downstream changes including when to stop the evaluation process. Given the impact on management and transplant decisions, we advocate for the widespread use of genetic testing in selected individuals undergoing transplant evaluation and donation who meet pre-defined criteria.